Elastic-Plastic Behavior of Compacted Loess under Direct and Cyclic Tension - Shixin He; Haibo Bai (Advances in Materials Science and Engineering)
Tensile strain is one of the main variables that affect fracturing in soil. This paper focuses on an experimental investigation of the deformation characteristics of remolded loess in direct and cyclic tension tests. The material behavior was approximated as elastic-plastic by ignoring the effect of time. In direct tests, the results showed that the change in slope of the stress-strain curve depended on the water content. The plastic constitutive relation was described by two methods. In cyclic loading and unloading tests, the remolded loess exhibited hysteresis (a phase lag), which led to dissipation of the mechanical energy. And no compaction limit phenomenon was found. A simple mathematical model was proposed to predict the plastic cyclic characteristics, and it was validated by the new test data.